A Biocultural Study on Gaoligongshan Pig (Sus scrofa domesticus), an Important Hog Landrace, in Nujiang Prefecture of China - Yanan Chu; Chen Lin; Zhuo Cheng; Xingcen Zhao; Yanxiao Fan; Binsheng Luo; Chunlin Long (Biology, 2022)
Over 80% proteins consumed by the local people in Nujiang Prefecture of Southwest China, a remote and mountainous area in the Eastern Himalayas, are from pork, or Gaoligongshan pig (a landrace of Sus scrofa domestica Brisson). Previous research on the Gaoligongshan pig has focused on nutritional composition, production performance, and genetic resource characteristics, but neglected the reasons behind the local people’s practice. From 2019 to 2022, we have used ethnobiological research methods to comprehensively document the traditional rearing and management patterns and the traditional culture associated with Gaoligongshan pigs. The results show that Gaoligongshan pigs graze in mixed herds with cattle and sheep during the day and prefer to eat 23 wild plant species, in which 17 species have medicinal values. At night, the pigs are artificially fed and rest in the pigsty. The local Bai and Lisu people have developed a creative food culture, rituals, and festivals culture associated with Gaoligongshan pigs. Overall, the biocultural diversity of Gaoligongshan pig contributes to the in situ conservation of genetic diversity of this important hog landrace, and supports rural development in this remote area.